Sociología de la conflictualidad urbana: Lima Metropolitana y la ciudad sostenible - Iziiga Nuñez, Roger (2007)
The present studv is (/ dialectic interpreuuion essav of urban problems in Peruvian societv. The urban question in Peru istull O[fI 11mero us contradicuons. conflicts and social tensions dile 10 the cliaracter und nature of our socioeconomicformation underdeveloped, dependeut. (JIU! dominated 1>1' tlte imperial power. transnational corporations. and servilc and dependen: (o ¡he./ál'l:igl1 interest bourgeoisic. AiI tltis IWl'.I'11(JIu] dramatic rcalitv is reflcctcd aru! condenses in the historic-structural problems a[l7ictillg(/1/1' /,('!-)///)/i('(111 societv. underdevelopment, sulnnission to the colonized powcr:politic elites -hcgemonic and dominant- ti rin,'?[or o[(ióu!ll'()r1d hUI gil'llI;? backs (o the rca! COI/mil' because they represen; a denutionalized politic al coste. statclcss QJ/dilld¡f.7'erellt 10 the Ii/e and work ~.conditious ofthe working classcs